PERAN PENGURUS KELOMPOK TANI HARAPAN MAKMUR DALAM MENGUBAH STATUS SOSIAL EKONOMI ANGGOTA - Yulas, Viktor (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThis thesis entitled ?The Roles of Management of Harapan Makmur farmer group in changing the socio-economic status of members in Mega Timur Village of Kubu Raya District?. The main problem in this research is what is The roles of Management of Harapan Makmur farmer group in changing the socio-economic status of members in Mega Timur Village of Kubu Raya District. Purposes of research are to know The Roles of Management of Harapan Makmur Farmer group in changing the socio-economic status of members in Mega Timur Village of Kubu Raya District.This reasearch applied a descriptive qualitative method. The research technique used was observation, interview, and documentation. The research result show that; The roles of Management of Harapan Makmur Farmer Group are (1) Interpersonal such as lead activities, (2) Informational such as sharing information from within and outside the group and (3) Decision Making such as making decision, policies and business management planning of the group. That Impact are (1)field of education, such us a more open, broader and more advanced mindset, fulfillment of the educational needs of the children members of the Harapan Makmur Farmer group.(2)Integration, such as increasing social network members, so it minimize social conflict.(3)Achievement of objectives such us achievement of the ideals of the group that is prosperity.(4)Economic,such as increasing revenues.Key words : The Roles of Management Farmer Group, Impact, Socio Economic Status